Harmoni Dalam Keberagaman: Toleransi di Kampung Jawa Muslim Dauh Puri Kaja Denpasar - Fina Izzatun Nufus; Dwi Setianingsih; Sukri S (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study examines the practice of tolerance and harmony that is manifested in the daily lives of the community in Kampung Jawa Muslim, Dauh Puri Kaja, Denpasar. This community is an example of the success of coexistence between the Muslim minority and the Hindu majority in the context of Bali’s multicultural society. Using a descriptive qualitative approach and historical data, this study traces the origins of the Javanese Muslim community, the role of community leaders, and forms of social interaction that reflect the values of tolerance. The results of the study show that harmony does not occur instantly, but is the result of a long process of adaptation, cross-cultural communication, and collective awareness of the importance of maintaining harmony. Kampung Jawa Muslim is a real model of tolerance based on local cultural roots and religion.